(3JMQjQ GdbhGYO GdefWbjI, aj TQM GdTeSjIs - (3GdQGRj GdJMJGfj, CHh YHO Gddg, bWH GdOjf, eMeO (B((3Ch eMehO(B) (3Hf eMeO, J (B677 (3g`s
(3ChdgG (B:s
(3Ef CHgi OQQ JfXe HfjGf GdHjGf (B...(3abO WGd EdMGM GdeTJZdjf Ydi GdeJQOOjf Edi HCf CTQM dge GdQSGdI GdTeSjI hCHjf ajg GdbhGYO GdefWjbI YdeG efge HCfge SCdh YQjfG eGgQG GSJeWQhG (B...s
(3BNQgG (B:s
... (3hbO jchf fhY ehVhY GdYde YQVG cbhfG cd NW eecf JfU jchf fhYg cbhdfG cd NjW jecf JfUjag aEf GdNW fhY ef GdebOGQ hbO jchf fhY ehVhY GdYde eY YQV PGJj (B... (3JeJs
(3GdJhKjbGJ GdeQLYjI (B:s
(3GdCYdGe (B7\38s
(3cTa GdXfhf (B2\1063s
(3eUOQ GbJfGA GdCUd (B:s
(3Ydj CejQjs
(3ehGUaGJ GdhYGA (B:s
Keywords: (3GdadSaI hGdefWbs